Specific Nucleic AcId Ligation for the detection of Schistosomes: SNAILS. - Alexander James Webb; Fiona Allan; Richard J R Kelwick; Feleke Zewge Beshah; Safari Methusela Kinung'hi; Michael R Templeton; Aidan Mark Emery; Paul S Freemont (Public Library of Science (PLoS), 2022)
Schistosomiasis, also known as bilharzia or snail fever, is a debilitating neglected tropical disease (NTD), caused by parasitic trematode flatworms of the genus Schistosoma, that has an annual mortality rate of 280,000 people in sub-Saharan Africa alone. Schistosomiasis is transmitted via contact with water bodies that are home to the intermediate host snail which shed the infective cercariae into the water. Schistosome lifecycles are complex, and while not all schistosome species cause human disease, endemic regions also typically feature animal-infecting schistosomes that can have broader economic and/or food security implications. Therefore, the development of species-specific Schistosoma detection technologies may help to inform evidence-based local environmental, food security and health systems policy making. Crucially, schistosomiasis disproportionally affects low- and middle-income (LMIC) countries and for that reason, environmental screening of water bodies for schistosomes may aid with the targeting of water, sanitation, and hygiene (WASH) interventions and preventive chemotherapy to regions at highest risk of schistosomiasis transmission, and to monitor the effectiveness of such interventions at reducing the risk over time. To this end, we developed a DNA-based biosensor termed Specific Nucleic AcId Ligation for the detection of Schistosomes or 'SNAILS'. Here we show that 'SNAILS' enables species-specific detection from genomic DNA (gDNA) samples that were collected from the field in endemic areas.